Personality at Work: The Drivers and Derailers of Leadership (Audio Book) - Warren, Ron (McGraw-Hill, 2017)
Personality matters. The actions and interactions between individuals have a huge impact on outcomes in the workplace, as in life. This impact is played out in every profession, at times with extraordinary and at times disastrous results.